PERFORMANCE ASSESSMENT OF CONVENTIONAL STEEL RISERGUARDS UNDER ACCIDENTAL IMPACT FOR OPERATIONS IN MALAYSIAN WATERS - PALANIANDY, DINESH KUMARAN (2015)
The operation of offshore platforms largely depends on the support it receive from offshore logistics, which come in the form ofoffshore support, service and supply vessels. These vessels make frequent trips to offshore platforms depending on the location, to provide essential supplies. Vessels approaching platforms for berthing increases the risk of a potential accidental collision with platform risers. Risers are overhanging pipelines which transport highly flammable oil and gas from the reservoir below seabed to the processing facilities on the platform. In view of that, platform operators in Malaysian waters have installed protective structures called riser-guards to prevent accidental impact on risers by operating vessels. The commissioning of riser-guards have resulted in several pre and post-installation issues which demand further design improvisation or development of an alternative protection system for risers. Prior to undertaking any design improvisation efforts, the currently employed conventional steel riser-guard must be analysed and its response to accidental impact must be studied. Lack of in-depth study and published materials on the response of conventional steel riser-guard to accidental vessel impact becomes the major motivation for undertaking this research. In this research, dynamic analysis is performed using the well-established finite element analysis methodology. The outcome ofthis dynamic analysis will be used to establish design criteria which will serve as a baseline for engineers to design an alternative system for the conventional steel riser-guard.